Conceptual system for sustainable and next-generation wastewater resource recovery facilities - YEŞİL, HATİCE; TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ (My University, 2023)
Shifting the concept of municipal wastewater treatment to recover resources is one of the key factors contributing to a sustainable society. A novel concept based on research is proposed to recover four main bio-based products from municipal wastewater while reaching the necessary regulatory standards. The main resource recovery units of the proposed system include upflow anaerobic sludge blanket reactor for the recovery of biogas (as product 1) from mainstream municipal wastewater after primary sedimentation. Sewage sludge is co-fermented with external organic waste such as food waste for volatile fatty acids (VFAs) production as precursors for other bio-based production. A portion of the VFA mixture (product 2) is used as carbon sources in the denitrification step of the nitrification/denitrification process as an alternative for nitrogen removal. The other alternative for nitrogen removal is the partial nitrification/anammx process. The VFA mixture is separated with nanofiltration/reverse osmosis membrane technology into low-carbon VFAs and high-carbon VFAs. Polyhydroxyalkanoate (as product 3) is produced from the low-carbon VFAs. Using membrane contactor-based processes and ion-exchange techniques, high-carbon VFAs are recovered as one-type VFA (pure VFA) and in ester forms (product 4). The nutrient-rich fermented and dewatered biosolid is applied as a fertilizer. The proposed units are seen as individual resource recovery systems as well as a concept of an integrated system. A qualitative environmental assessment of the proposed resource recovery units confirms the positive environmental impacts of the proposed system.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ÇEVRE; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ENVIRONMENTAL; Çevre Mühendisliği; Fizik Bilimleri; Çevre Kimyası; Atık Yönetimi ve Bertarafı; Kirlilik; Environmental Engineering; Physical Sciences; Environmental Chemistry; Waste Management and Disposal; Pollution; Biogas; Bioplastics; Environmental sustainability; Resource recovery; Volatile fatty acids